2014
DOI: 10.1136/archdischild-2014-307384.568
|View full text |Cite
|
Sign up to set email alerts
|

PS-268 Stool Characteristics And Gastrointestinal Tolerance Of Chinese Infants Fed Term Formula Containing Increased Sn-2 Palmitate And Oligofructose: An Observational Study

Abstract: Background The feeding scheme of premature newborns changed in recent years. The latest recommendations emphasise the intensification both of parenteral and enteral nutrition from the first days of life. Methods We compared two groups of VLBW newborns born in our institution in 2010 and 2013. We analysed how the changes of our nutritional treatment influenced chosen parameters in both groups of newborns. Changes included: more intensive full TPN from first hours of life, earlier enteral nutrition (EN), faster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Parents were free to switch their infant to other feeding regimens at any time during the study. Continued follow-up of these infants depended on the new feeding regimen and the timing of the switch relative to study days 15–17 (when parents completed the second of several three-day diaries on infant stool characteristics, another study outcome reported separately [ 19 ]). If the infant was switched to another of the three study feeding regimens (e.g., from exclusively breastfed to mixed-fed with study formula and breast milk) before the completion of the second three-day infant stool diary, the infant continued to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Parents were free to switch their infant to other feeding regimens at any time during the study. Continued follow-up of these infants depended on the new feeding regimen and the timing of the switch relative to study days 15–17 (when parents completed the second of several three-day diaries on infant stool characteristics, another study outcome reported separately [ 19 ]). If the infant was switched to another of the three study feeding regimens (e.g., from exclusively breastfed to mixed-fed with study formula and breast milk) before the completion of the second three-day infant stool diary, the infant continued to participate in the study.…”
Section: Methodsmentioning
confidence: 99%